Paclitaxel-Ifosfamide-based Therapy as Salvage Treatment in Platinum-resistant Recurrent/Metastatic Head and Neck Cancer - CHOU, MING-YU; WU, WEN-CHI; CHU, PEN-YUAN; TAI, SHYH-KUAN; CHANG, PETER MU-HSIN; LEE, TSUNG-LUN; CHEN, TIEN-HUA; YANG, MUH-HWA (In vivo (Athens), 2024)
Treatment options are limited, and the prognosis is poor for patients with platinum-resistant recurrent metastatic (R/M) head and neck squamous cell carcinoma (HNSCC). This study evaluated the efficacy and safety of a paclitaxel and ifosfamide (TI) regimen in patients with R/M HNSCC whose disease had progressed following platinum-based therapy. In this retrospective study, we included 53 patients with R/M HNSCC who underwent at least one cycle of TI-based therapy, post platinum failure, between February 2020 and August 2023. Some patients received the TI regimen in combination with immunotherapy and/or cetuximab. Key metrics assessed included the objective response rate (ORR), disease control rate, and progression-free as well as overall survival. The study observed an ORR of 15.8% and a disease control rate of 36.8%. The median progression-free survival for the entire cohort was 3.3 months, and the median overall survival was 9.6 months. Notably, the combination of TI with immunotherapy yielded a higher ORR of 30.8%, compared to 14.3% with TI alone. The most prevalent grade 1-2 adverse events were anemia (81%), weight loss (68%) and hypernatremia (55%). The TI-based regimen demonstrated favorable efficacy and safety profile in treating R/M HNSCC. Enhanced outcomes may be attainable when combining it with immunotherapy. This study suggests that TI-based therapy could serve as a potential salvage option for this specific patient group.